The Success experience of Bangladesh Pharmaceutical Industry: Strategies & Development - Lalmi, Hocine; Abid, Khedidja (Milev Journal of Research and Studies, 2019)
This paper reports a case study of the successful development of the pharmaceutical industry in Bangladesh and the critical roles played by the country’s National Drug Policy established in 1982 in boosting this development. The success story of the Bangladesh pharmaceutical sector is very pleasant. It had to travel a long way to achieve the present prestigious position in domestic and international markets. By now (2018), 97% of country’s demand of medicines is produced locally mainly by national pharmaceutical companies, and exporting around US$ 97 million. The pharmaceutical sector of Bangladesh is expanding rapidly and some companies have already certified by different international regulatory authorities like UK-MHRA, Australia-TGA, EU, etc. for quality management and quality products manufacturing. One might wonder why the pharmaceutical industry, which seems to be a capital-intensive, high-tech industry, can be developed in a low-income country like Bangladesh. This paper attempts to explain what characterize the National Drug Policy as an industrial policy, how successful the development of this industry has been since 1982, and to what extent did the pharmaceutical industry contribute to the economic development, then compare it to what was done in Algeria.